Surface Acoustic Wave-Based Microfluidic Coagulation Device for Monitoring Anticoagulant Therapy - Harder, Sebastian; Santos, Sascha Meyer dos; Krozer, Viktor; Moll, Jochen (Seminars in Thrombosis and Hemostasis, 2019)
An universal coagulation test that reliably detects prolonged coagulation times in patients, regardless of which anticoagulant is administered, is not yet available. The authors developed a novel, miniaturized device utilizing surface acoustic waves (SAW) to detect clotting, and used it to develop a novel universal microfluidic coagulation test. Results from this assay were compared with results from standard coagulation assays to detect classical anticoagulants (unfractionated heparin, argatroban) and direct oral anticoagulants (dabigatran, rivaroxaban). The SAW-clotting time (SAW-CT) of this novel device was prolonged in a dose-dependent manner for heparin, argatroban, dabigatran, and rivaroxaban, comparable to standard assays. The authors confirmed the clinical utility of this device in a small patient population admitted to a stroke unit. Preliminary clinical data prove the suitability of the SAW-CT in patients receiving warfarin, rivaroxaban, or dabigatran. The device could be particularly useful as a point-of-care test to assess whole blood coagulation (e.g., in stroke units or in other emergency settings).
Keywords: drug monitoring; surface acoustic waves; anticoagulation